The Independent Curriculum is Viewed From the Thoughts of KH. Hashim Ash'ari - Harahap, Norlan Cahaya; Srg, Kimlansyah Romadan; Rambe, Samia (Fahmina: Jurnal Pendidikan Islam, 2023)
Through one of the fiqur figures of Indonesian scholars KH. Hashim Asha'ari. The contribution of his thoughts to the sustainability of Islamic Education in the country should be used as a reference for the future. Islamic religious education that he hopes is able to master and can be carried out in continuous practice from both a teacher and a student, so that the purpose of education he hopes can be a provision in the happiness of the world and the hereafter. KH. Hashim Asha'ari tirelessly in studying religion both domestically and abroad to the city of Mecca can be used as a motivation to fight for the values of Islamic Education today. The results of this study reveal the concept of independent learning policy offered by KH. Hashim Asha'ari, including: first, learning according to the field of science and competence. Second, self-learning activities aim to create a generation that is loyal, pious, noble character, more creative, the ability to work together, global characteristics of diversity, critical thinking, and independence. Third, KH. Hashim Asha'ari also develops literacy potential by reviewing various reference materials. Fourth, improve the ability of educators. Furthermore, this research is expected to strengthen the independence of studying the curriculum from the perspective of Islamic education leaders.